The Advanced Students’ Motivation for Explicit Learning of Grammar - Jankowska, Aleksandra (Wydawcnictwo Naukowe UAM, 1988)
The role of the explicit teaching and learning of grammar in the process of foreign language teaching is a very controversial issue. Language teachers and language teaching methodologists differ in their opinions as to whether grammar should be taught at all and, if so, what is the best way of presenting it. In order to find out students’ opinions on the usefulness of the explicit teaching and learning of grammar a questionnaire was given to fifty-one English majors studying in the Institute of English at Adam Mickiewicz University in Poznań. The results of the questionnaire reveal a very positive attitude on the part of the students towards the explicit learning of grammar. The deductive way of learning seems to be favoured by the majority of the respondents, who also unanimously point to translation as a very effective form of grammar exercise.